Electrochemical aptamer scaffold biosensors for detection of botulism and ricin toxins. Issue 82 (1st September 2015) - Fetter, Lisa; Richards, Jonathan; Daniel, Jessica; Roon, Laura; Rowland, Teisha J.; Bonham, Andrew J.
Abstract : Electrochemical aptamer biosensors for ricin and botulinum neurotoxins are reported, with strategies for generalized biosensor design. Abstract : Protein toxins present considerable health risks, but detection often requires laborious analysis. Here, we developed electrochemical aptamer biosensors for ricin and botulinum neurotoxins, which display robust and specific signal at nanomolar concentrations and function in dilute serum. These biosensors may aid future efforts for the rapid diagnosis of toxins.